THE EFFECTIVENESS OF IMPLEMENTING HR AND DIGITAL MANAGEMENT IN GENERAL EDUCATION SCHOOLS (International journal of artificial intelligence, 2025)
This article examines the effectiveness of implementing human resource (HR) and digital management systems in general education schools. Through comprehensive literature analysis and personal analytical evaluation, the study explores how modern HR practices combined with digital technologies enhance administrative efficiency, teacher performance, and educational outcomes. However, successful implementation requires adequate infrastructure, training, and change management strategies.